Agentic traits, even when perceived as low value, still hold sway in management. Issue 3 (3rd April 2022) - Agut, Sonia; Hernández Blasi, Carlos; Pinazo, Daniel
ABSTRACT: Role congruity theory postulates that traditionally there is a mismatch between the communal qualities associated with women and the masculine or agentic qualities considered necessary in a good leader. Thus, female candidates are presumed to be less suitable for leadership roles. The purpose of this study is to discover the conditions under which this (in)congruity may fluctuate. In a hypothetical manager recruitment process done in Spain, two profiles (agentic and communal) were associated with female and male candidates to explore variations according to the organizational setting (profit-oriented or civic-minded company) and the value attributed to candidates' qualities (high or low). Results showed congruity between candidates' profile and organizational setting when their trait value was high: agentic candidates were preferred over communal candidates for the profit-oriented company, with the reverse occurring for the civic-minded company. However, candidates' sex apparently played no significant role in participants' decision making; additionally, when the value of candidates' traits was low, congruity was only found for the profit-oriented company. We conclude that, overall, the agentic construal of management, with its good and bad features, still has the upper hand in the current vision of leadership.